2013
DOI: 10.18061/1811/54894
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Capital for Amish Entrepreneurs in Pursuing Informal Economic Opportunities

Abstract: This study explores the specific types of social relationships that influence initiation into and involvement in informal businesses. In particular, it examines the social capital possessed by Amish entrepreneurs who establish home-based, off-the-books tourism businesses. This paper theoretically refines social capital by identifying three dimensions of social relations: cognitive, reciprocal, and structural. I explore the relationship between social capital and Amish involvement in tourism businesses by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…Despite the success of many Amish-run businesses, the chain and box stores worried many small business owners. Jeong (2013) found that Amish businesses could thrive because of connections to non-Amish tourist trade agents. Accordingly, many Amish-run business owners seemed to understand that they needed to cater to the wants of the tourist trade by creating atmospheres that met the expectations of these customers, stores that have a "Pennsylvania Dutch" flavor.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the success of many Amish-run businesses, the chain and box stores worried many small business owners. Jeong (2013) found that Amish businesses could thrive because of connections to non-Amish tourist trade agents. Accordingly, many Amish-run business owners seemed to understand that they needed to cater to the wants of the tourist trade by creating atmospheres that met the expectations of these customers, stores that have a "Pennsylvania Dutch" flavor.…”
Section: Discussionmentioning
confidence: 99%
“…Modal sosial berpotensi menjadi strategi dan sarana untuk mengembangkan usaha kecil (Schwarz, 2017;Turner, 2007;Jeong, 2013). Keefektifan modal sosial sangat ditentukan oleh ukuran koneksi jaringan yang dapat dimobilisasi oleh tiap individu (Turner, 2007).…”
Section: Pengantarunclassified
“…While we gain insight into the type of outcomes made possible by a group of social mechanisms, it is less clear what particular work trust is doing to produce stability. Stepping outside of a social capital framework allows for an approach suited to distinguishing interactional mechanisms, like trust, from the social ties or networks through which they flow (Jeong 2013).…”
Section: The Role Of Trust In the Informal Sectormentioning
confidence: 99%